Teaching digital literacies - Bloch, Joel; Wilkinson, Mark J. (English language teacher development series., 2014)
Teaching Digital Literacies explores different approaches to teaching digital literacies in the second language classroom. The authors provide a comprehensive overview of literacy and the new technologies in an easy to follow guide that language teachers will find very practical for their own contexts. Topics covered include different and multiple forms on literacy including web 1.0 and web 2.0, blogging and Twitter, multimodal literacy, social networking, mobility and digital literacy, as well as assessment of digital literacies. Teaching Digital Literacies is a valuable addition to the literature in our profession.